THE IMPACT OF PICTURE PROMPTS ON STUDENTS’ ABILITY IN SUBJECT-VERB AGREEMENT: A CLASSROOM ACTION RESEARCH - Mintarsih, Mintarsih; Yani, Ani (IJIET (International Journal of Indonesian Education and Teaching), 2024)
This study aims to find out how the impact of picture prompts can improve the ability of seventh-grade students at SMPN 121 Jakarta regarding the use of subject-verb agreements in simple present tense sentences. Observation before action was carried out in class VII SMPN 121 Jakarta. From the data collected through observation and prerequisite tests before entering a new chapter, it is known that the students have difficulty answering subject-verb agreement questions in simple present-tense sentences. In addition, not all the students are facilitated by gadgets. For this reason, the researchers uses pictures that can be used both electronically and paper-based to encourage students' ability to subject-verb agreement. This research was conducted using the Classroom Action Research method which focused on solving the problems encountered. The use of pictures as a learning medium in English is expected to encourage the students to more easily understand the subject-verb agreement material. From the findings, reports on the student learning outcomes, and observations it can be said that the use of pictures is quite effective in improving students' ability to subject-verb agreement material in simple present tense sentences.